TINJAUAN HUKUM TERHADAP PENGGUNAAN TENAGA KERJA ASING DI INDONESIA BERDASARKAN PERATURAN PRESIDEN NOMOR 20 TAHUN 2018 JO. PERATURAN MENTERI KETENAGAKERJAAN NOMOR 10 TAHUN 2018 - S Atalim; Shierly Debora (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2019)
Indonesia is a legal state.Developing countries where development of technology is growing rapidly.So the country has high competitiveness to work. Then, the Government issued a new regulation governing Manpower, namely Presidential Regulation 20 Year 2018 concerning the Use of Foreign Workers, followed by its implementing regulation namely Minister of Manpower Regulation 10 year 2018 concerning Procedures for the Use of Foreign Workers, which replacing the old regulation namely Presidential Regulation 72 of 2014 concerning the Use of Foreign Workers and its implementing regulations, namely Minister of Manpower Regulation No. 35 of 2015. However, after the issuance of the latest regulations governing Manpower there were pros and cons, the pros against new regulations this is because since the latest regulation, the users of foreign labor have easy access to the terms of use of foreign workers. As for the contract, because workers in Indonesia feel that since the latest regulation, Indonesian workers feel their chances of working are fewer. So that the author writes about the problem of how the Regional Government policies in the use of foreign workers? The author uses normative legal methods and uses interview data and survey results as supporting data.The results of the research obtained are that the Government has taken a policy that is very helpful for the progress of the national economy in our country, only there are some problems in enforcing the regulations in the community there are still shortcomings.